ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENAWARAN DAN PERMINTAAN KREDIT MODAL KERJA PADA BANK UMUM DI SUMATERA BARAT - Amelia, Noli; Aimon, Hasdi; Syofyan, Efrizal (Program Studi Magister Ilmu Ekonomi, 2015)
This study aimed to analyzed (1). The effect of third party funds, risk of credit(NPL), and interest rate for credit suply of venture capital to the comercial bank in West Sumatera, (2). The effect of economics, interest rate, inflation, and kurs for credit demand Â of venture capital to the comercial bank in West Sumatera, (3). The effect third party funds, risk of credit (NPL), economics, inflation, and kurs for interest rate of venture capital to the comercial bank in West Sumatera. This study included type of descriptive and asotiatif. Data in the form of time series of the first quarter of 2000 to te third quarter of 2014. This study using a simultaneous equations models analysis in form of Indirect Least Square (ILS). Endogen variables is credit suplay, credit demand, and interest rate. And eksogen variables is third party funds, risk of credit (NPL), economics, inflation and kurs. The research concludes that (1). third party funds, risk of credit (NPL), and interest rate have a significant effect on credit suply of venture capital to the comercial bank in West Sumatera, (2). Inflation and interst rate have a significant effect on credit demand of venture capital to the comercial bank in West Sumatera,while economic and kurs have not a significant effect on credit demand of venture capital to the comercial bank in West Sumatera. (3) Risk of credit (NPL), economics, inflation, and kurs have a significant effect for interest rate of venture capital to the comercial bank in West Sumatera, while third party funds have not a significant effect interest rate of venture capital to the comercial bank in West Sumatera.Keywords : credit suply, credit demand, interest rate, third party funds, risk of credit (NPL), economics, inflation, and kurs